2017
DOI: 10.1016/j.jpeds.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Biomarkers of Placental Maternal Vascular Underperfusion Predict Bronchopulmonary Dysplasia-Associated Pulmonary Hypertension

Abstract: Objective To assess whether cord blood biomarkers associated with placental maternal vascular underperfusion (MVU) are predictive of bronchopulmonary dysplasia-associated pulmonary hypertension (BPD-PH). Study design Premature infants enrolled in a longitudinal cohort study were randomly sampled from 4 gestational age strata (n = 190, range 23–36 weeks). Fifteen factors from a human angiogenesis panel were measured in cord blood using multiplex immunoassay. Multivariate linear regression was used to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 40 publications
2
53
0
Order By: Relevance
“…Similarly, endostatin (ES): angiopoietin‐1 (Ang‐1) ratio on day of life 7 may also be useful as a biomarker for early PH‐risk prediction in patients with severe BPD . Lastly, placental growth factor (PIGF) and NT‐proBNP have also shown potential as biomarkers for PH in BPD . Furthermore, there are likely biomarkers that have not yet been identified, so there is a place for unbiased evaluation of genome wide associations for PH in BPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, endostatin (ES): angiopoietin‐1 (Ang‐1) ratio on day of life 7 may also be useful as a biomarker for early PH‐risk prediction in patients with severe BPD . Lastly, placental growth factor (PIGF) and NT‐proBNP have also shown potential as biomarkers for PH in BPD . Furthermore, there are likely biomarkers that have not yet been identified, so there is a place for unbiased evaluation of genome wide associations for PH in BPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mestan et al also convincingly demonstrate that cord blood biomarkers, including placental growth factor, granulocyte colony stimulating factor, and VEGF factor A are decreased in association with striking placental findings of MVU and were further associated with subsequent diagnoses of BPD and PH. 21 Most importantly, placental growth factor and granulocyte colony stimulating factor were markedly decreased in a second validation cohort as well, further supporting the concept that cord blood angiogenic factors are decreased with placental MVU and may be very early predictors of BPD-PH risk. In addition, the authors speculate that disruption of placentation and vascular perfusion represents failed angiogenesis, as reflected by these biomarkers, and that abnormal developmental angiogenesis may reflect abnormalities of vascular signaling that contribute to postnatal disease.…”
Section: See Related Article P 33mentioning
confidence: 53%
“…In this volume of The Journal, Mestan et al 21 provide exciting new information that extends past observations and links abnormalities of placental structure with high risk for BPD and BPD with pulmonary hypertension (PH). This team and others have established the concept that placental vascular structural abnormalities related to hypertensive disorders of pregnancy and preeclampsia are strongly associated with fetal growth restriction and that examination of placental tissue for vascular lesions that reflect maternal underperfusion (MVU) after preterm birth provides a unique and very solid approach to predict the subsequent risk for BPD and PH.…”
Section: See Related Article P 33mentioning
confidence: 81%
“…VEGF is expressed in villous and extravillous trophoblasts and its expression level alters with adverse pregnancy outcomes [43]. It has been observed that pregnancies with placenta that demonstrated severe vascular under-perfusion were strongly associated with lower levels of proangiogenic factors in UCB, such as VEGF and its soluble receptor sVEGFR-2 [44]. It was found that resident placental endothelial cells from pregnancies characterized by fetal growth restriction resulting in preterm delivery, demonstrated decreased angiogenesis with impaired signaling in different VEGF pathways, including activation of the VEGF-NO signaling [45].…”
Section: Discussionmentioning
confidence: 99%